2010
DOI: 10.1172/jci39534
|View full text |Cite
|
Sign up to set email alerts
|

HOXA9 regulates BRCA1 expression to modulate human breast tumor phenotype

Abstract: Breast cancer 1, early onset (BRCA1) expression is often reduced in sporadic breast tumors, even in the absence of BRCA1 genetic modifications, but the molecular basis for this is unknown. In this study, we identified homeobox A9 (HOXA9) as a gene frequently downregulated in human breast cancers and tumor cell lines and noted that reduced HOXA9 transcript levels associated with tumor aggression, metastasis, and patient mortality. Experiments revealed that loss of HOXA9 promoted mammary epithelial cell growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 107 publications
4
97
0
2
Order By: Relevance
“…The HOXA cluster has been related with normal development of urogenital tracts (Burel et al, 2006); in particular, HOXA9 and -11 are important in controlling the embryonic development of Müller ducts (Hsieh-Li et al, 1995). With regard to HOXA9, this gene has been found overexpressed in hematological malignancies (Milne et al, 2010){Zhao, 2014 #203}, but in solid tumors, especially epithelial tumors, it has been observed as downregulated (Gilbert et al, 2010;Chen et al, 2012;Hwang et al, 2015). These observations were in agreement with our observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The HOXA cluster has been related with normal development of urogenital tracts (Burel et al, 2006); in particular, HOXA9 and -11 are important in controlling the embryonic development of Müller ducts (Hsieh-Li et al, 1995). With regard to HOXA9, this gene has been found overexpressed in hematological malignancies (Milne et al, 2010){Zhao, 2014 #203}, but in solid tumors, especially epithelial tumors, it has been observed as downregulated (Gilbert et al, 2010;Chen et al, 2012;Hwang et al, 2015). These observations were in agreement with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…The tumor suppressor function of HOXA9 has been extensively investigated in breast cancer, where it has been shown that HOXA9 directly regulates BRCA1 and other genes involved in invasion, growth, and metastasis (Gilbert et al, 2010). Uchida et al observed that high methylation levels of HOXA9 are associated with a high risk of metastatic tumors; in addition, the authors found that reduced HOXA9 expression confers an advantage on cell growth (Uchida et al, 2014); these observations are consistent with our results in CC-derived cells.…”
Section: Discussionsupporting
confidence: 90%
“…HOXA9 expression is spatially and temporally regulated during hematopoiesis and embryonic development. Reduced HOXA9 transcript levels are reportedly associated with breast cancer aggression, metastasis and patient mortality (31). ARID1A also directly interacts with HIC1 (hypermethylated in cancer 1), a tumor suppressor gene, which is epigenetically inactivated in numerous human cancers (32,33).…”
Section: Identification Of Arid-containing Proteins and Arid1a-interamentioning
confidence: 99%
“…The HOXA9 (homeobox A9) gene encodes a sequence-specific transcription factor which is part of a developmental regulatory system that provides cells with specific positional identities on the anterior-posterior axis of an organism (The NCBI handbook, 2002). Dysregulated expression of HOXA9 has been described in several malignancies including non-small-cell lung cancer (Calvo et al, 2000) and breast cancer (Gilbert et al, 2010). Neuroblastoma cell lines treated with demethylating agents have been reported to display increased levels of HOXA9 gene expression (Margetts et al, 2008).…”
Section: Apoptosis-related Genesmentioning
confidence: 99%